Identifying Level of Historical Consciousness on College Students of History Education In Terms of Ethnicity - Aisiah Aisiah; Sumarno Sumarno (Faculty of Social Science, Universitas Negeri Padang, 2017)
The purpose of this study was to identify the level of historical consciousness on college students in Indonesia in terms of ethnic groups, particularly Javanese and Minangkabau ethnics. Historical consciousness is measured by four aspects, namely knowledge of historical events, understanding of historical research methods, finding meaning of historical events, and viewing historical usefulness. Subjects in this study were Javanese college students, represented by history education college students at State University of Yogyakarta and Minangkabau college students represented by history education college students at Padang State University. The research data were collected through historical consciousness test. Test instruments were formulated in the form of multiple choice questions associative consisting of knowledge about historical events, understanding of historical research methods, finding meaning of historical events and viewing usefulness of history. The data were analyzed by the percentage of the average scores level of historical consciousness on both ethnics group of college students. Overall, result analysis showed that percentage score of historical consciousness of Javanese college students is 42% higher than college student of Minangkabau i.e.39%. It means that the level of historical consciousness of Javanese college students higher than Minangkabau college students.T-test result shows that, at df = 68, value sig. 0.182 < 0.05, it means that level of historical consciousness between Javanese college students and Minang did not differ significantly. It can be said that the level of historical consciousness of Javanese college students was equal to Minang college students.